“Sit, Guest of Faith”: Can Orthodox Zionist Thought Craft a Positive Yet Subversive Dialogue with Christianity? Karma Ben-Johanan’s "Jacob’s Younger Brother: Christian-Jewish Relations after Vatican II" - Meyer, David (Studies in Christian-Jewish Relations, 2023)
No abstract is available.